The Preliminary Sedimentation Pattern Study in West Borneo NPP Potential Site - Alhakim, Euis E; Ryanto, Theo A; Susiati, Heni; Suntoko, Hadi (Indonesian Journal of Geography, 2024)
Coastal environmet dynamics study is one of the NPP site feseability studies that need to be conducted to understand the potential external risk in an NPP development. The Pantai Gosong area was the preferred potential site for the NPP development and was located in the coastal area. Therefore, external factors such as abrasion or sedimentation would influence the NPP site. This research studied the sedimentation pattern of the Pantai Gosong coastal area based on the landform analysis. The results showed that the landform in the Pantai Gosong area was classified as a highly eroded hill, lowly eroded footplain, natural levee-back swamp, beach ridge, alluvial plain, and coastal alluvial plain. The sedimentation process in the northern coastal area of Pantai Gosong that has lowly eroded footplain landform was more intense than in the southern part. The analysis was well correlated with the estimated sediment thickness from the microtremor method analysis that showed that the northern coastal area has higher sediment deposits with 12.7 to 21.7 m of thickness than the southern coastal area with 3.2 to 12.6 m thickness. The northern footplain in the Pantai Gosong coastal area was expected to have higher sedimentation than the southern part continuously